Online Impulsive Buying Behavior (OIBB) Influenced by Hedonism, Re-source Availability, and Shopping Convenience Moderated by the Ease of Using Digital Payment Methods - Dhewayanti, Elisabeth Krisna; Dahlan, Kandi Sofia (Eduvest - Journal of Universal Studies, 2023)
This research focuses on the influence of hedonism, resource availability, and shopping convenience online impulsive buying behavior (OIBB), moderated by ease of use of digital payment methods. Data was collected by distributing questionnaires to 356 respondents online. 340 respondents were selected to be the sample because they fit the specified respondent criteria. The data obtained was analyzed using the PLS-SEM method and processed using SmartPLS software version 4.0. This research shows that hedonism and the convenience of shopping directly positively and significantly influence online impulsive buying behavior. Meanwhile, the availability of resources (money) does not significantly influence online impulsive buying behavior. In the moderation relationship, ease of use of e-wallets strengthens the relationship between hedonism and online impulsive buying behavior. Still, it can decrease the relationship between shopping convenience and online impulsive buying behavior. Meanwhile, the ease of use of e-wallets does not influence the relationship between the availability of funds and online impulsive buying behavior.